Are current analytical methods suitable to verify VITAL® 2.0/3.0 allergen reference doses for EU allergens in foods?. (November 2020) - Holzhauser, Thomas; Johnson, Philip; Hindley, James P.; O'Connor, Gavin; Chan, Chun-Han; Costa, Joana; Fæste, Christiane K.; Hirst, Barbara J.; Lambertini, Francesca; Miani, Michela; Robert, Marie-Claude; Röder, Martin; et al.
Abstract: Food allergy affects up to 6% of Europeans. Allergen identification is important for the risk assessment and management of the inadvertent presence of allergens in foods. The VITAL® initiative for voluntary incidental trace allergen labeling suggests protein reference doses, based on clinical reactivity in food challenge studies, at or below which voluntary labelling is unnecessary. Here, we investigated if current analytical methodology could verify the published VITAL® 2.0 doses, that were available during this analysis, in serving sizes between 5 and 500 g. Available data on published and commercial ELISA, PCR and mass spectrometry methods, especially for the detection of peanuts, soy, hazelnut, wheat, cow's milk and hen's egg were reviewed in detail. Limit of detection, quantitative capability, matrix compatibility, and specificity were assessed. Implications by the recently published VITAL® 3.0 doses were also considered. We conclude that available analytical methods are capable of reasonably robust detection of peanut, soy, hazelnut and wheat allergens for levels at or below the VITAL® 2.0 and also 3.0 doses, with some methods even capable of achieving this in a large 500 g serving size. Cow's milk and hen's egg are more problematic, largely due to matrix/processing incompatibility. An unmet need remains for harmonized reporting units, available reference materials, and method ring-trials to enable validation and the provision of comparable measurement results. Highlights: Methods that detect clinically relevant reference doses of allergens are required. Methods: Peanuts, soy, hazelnut, wheat, cow's milk, hen's eggs reviewed in detail. ELISA, qPCR, and MS revealed method specific advantages and limitations. Sensitive methods for the verification of VITAL® 2.0/3.0 reference doses exist. Comparability demands harmonized units, reference materials and method ring-trials.